Social, Environmental and Economic Impact Assessment of COVID-19 on Rural Tourism - Eslami, Fatemeh; Namdar, Razieh (Frontiers in Public Health, 2022)
Today, various solutions have been proposed to improve the economic situation of villages and deprived areas, among which tourism is known as the best solution for those areas with the necessary potentials for tourism development. On other hand, the COVID-19 pandemic had significant effects on human life worldwide. The prevalence of COVID-19 has caused a lot of damage to different sectors of the global economy, but without a doubt, the rural tourism industry should be considered among the economic activities that have suffered the most from this virus. In this study, with the aim of investigating these effects on the rural tourism industry, it has been analyzed and compared in three important economic, social and environmental dimensions before and after the outbreak of the COVID-19. This quantitative study was used survey method. The statistical population of the study consisted of local stakeholders of rural tourism and experts of the relevant organizations in Natanz county of Iran. The results of confirmatory factor analysis indicate that the constructs used in the model have appropriate and acceptable fit. The results of the study also, showed that the prevalence of COVID-19 has adverse consequences including reducing the desirable economic and social effects of tourism mentioned among both groups of experts and rural stakeholders. from rural tourism stakeholders' opinion, environmental variables of the tourism areas before and after the COVID-19 was different, and in the absence of tourists in this area, the destructive environmental effects have strongly decreased.